MEDIA PEMBELAJARAN E-LEARNING DALAM PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DI SMA LABORATORIUM PERCONTOHAN UPI BANDUNG - Ramdani, Rijki; Rahmat, Munawar; Fakhruddin, Agus (Universitas Pendidikan Indonesia, 2018)
The Internet can be used as a way to transfer knowledge from teacher to student. E-learning is one of learning media which uses internet. The purpose of this research is to describe and analyze: (1) the learning planning; (2) the learning process; (3) the learning evaluation; (4) the learning process results of Islamic Education learning with e-learning. This research uses qualitative approach and descriptive method. The data collection technique are interviews, observation, and study of documentation. This research was conducted in SMA Laboratorium Percontohan UPI Bandung who have used e-learning as a learning media. Based on the results of the research, it was found that the learning planning of Islamic Education learning with e-learning is not much different with no use of e-learning. The learning implementation process of Islamic Education learning with e-learning is conducted by the method of lecture that assisted with e-learning as a students learning resource centre. Learning evaluation of Islamic Education learning with e-learning is done in the moment after the sub chapter materials have been studied by students with automated systems in e-learning. The results of the learning process of Islamic Education learning with e-learning effect on student learning outcomes. The influence is only experienced on the competence of knowledge, while attitude and skills there is no correlation.Â Internet dapat dijadikan cara untuk transfer pengetahuan dari guru kepada siswa. Pembelajaran yang memanfaatkan internet salah satunya adalah media pembelajaran e-learning. Tujuan penelitian ini untuk mendeskripsikan dan menganalisis: (1) perencanaan pembelajaran; (2) proses pembelajaran; (3) evaluasi pembelajaran; (4) hasil proses pembelajaran PAI dengan e-learning. Penelitian ini menggunakan pendekatan kualitatif dan metode deskriptif. Teknik pengumpulan data dilakukan dengan cara wawancara, observasi dan studi dokumentasi. Penelitian ini dilakukan di SMA Laboratorium Percontohan UPI Bandung yang telah menggunakan media pembelajaran e-learning. Berdasarkan hasil penelitian, ditemukan bahwa perencanaan pembelajaran PAI dengan e-learning tidak jauh berbeda dengan tidak menggunakan e-learning. Proses pelaksanaan pembelajaran PAI dengan e-learning dilakukan dengan metode ceramah yang dibantu dengan media pembelajaran e-learning sebagai pusat sumber belajar siswa. Evaluasi pembelajaran PAI dengan e-learning dilakukan pada saat setelah sub bab materi telah dipelajari oleh siswa dengan sistem otomatis pada e-learning. Hasil proses pembelajaran PAI dengan e-learning berpengaruh terhadap hasil belajar siswa. Pengaruh tersebut hanya dialami pada kompetensi pengetahuan saja, sedangkan sikap dan keterampilan tidak ada korelasinya.